TCreation Music Bangsing Waringin | Tabuh Kreasi Bangsing Waringin - I Gede Wisnu Kusumayana; Saptono - (GHURNITA: Jurnal Seni Karawitan, 2023)
Bangsing Waringin comes from two words in Balinese Alus, namely Bangsing and Waringin, "Bangsing" which means Root or Wood while "Waringin" which means banyan or the name of the tree itself. From this concept, the stylists put the idea into the gamelan Angklung Don Kutus with the title percussion creation of Bangsing Waringin. This piece of percussion composition created by Bangsing Waringin emphasizes melodic, rhythmic, dynamic and harmonic patterns. This work describes the robustness and complexity of the banyan tree itself, which has existed for centuries until now and also directly illustrates the benefits of the banyan tree in Kayuputih Village. This creation's tabuh is contemporary but still refers to traditional patterns or grips such as the tri angga with three main frameworks namely kawitan, pengawak, and retailer. Apart from these three main frameworks, the stylist prefers patterns by mentioning divisions in the composition of this creation's percussion accompaniment. The stylist cultivates playing techniques on the pemade instrument, jublag melodies, jegogan and flute, by using more diatonic melodic playing, polyphonic techniques, and kebyaran playing on the accompaniment part.